2008
DOI: 10.1038/ki.2008.210
|View full text |Cite
|
Sign up to set email alerts
|

Pravastatin improves renal ischemia–reperfusion injury by inhibiting the mevalonate pathway

Abstract: Statins are known to lessen the severity of renal ischemia-reperfusion injury. The present study was undertaken to define the mechanism of renoprotective actions of statins using a mouse kidney injury model. Treatment of mice with pravastatin, a widely used statin, improved renal function after renal ischemia-reperfusion without lowering the plasma cholesterol level. Administration of pravastatin with mevalonate, a product of HMG-CoA reductase, eliminated renal protection suggesting an effect of pravastatin on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 52 publications
3
52
1
Order By: Relevance
“…12,13 Studies using animal models have shown that giving statins before an ischemic event significantly reduces AKI. [8][9][10][11][12][13][14] Whether a similar benefit occurs in humans is uncertain. Some observational studies have shown that statins are associated with less AKI, whereas others have not.…”
mentioning
confidence: 99%
“…12,13 Studies using animal models have shown that giving statins before an ischemic event significantly reduces AKI. [8][9][10][11][12][13][14] Whether a similar benefit occurs in humans is uncertain. Some observational studies have shown that statins are associated with less AKI, whereas others have not.…”
mentioning
confidence: 99%
“…Campos et al (11) showed that kidney dysfunction after renal I /R tended to be less severe in rats fed a cholesterol-supplemented diet for 3 weeks before the insult than in control rats fed a regular diet over that period. Recently, we observed that although serum creatinine concentration after renal I/R did not differ between ApoE−/− and control mice, I/ R injury judged by histopathological analysis was less severe in the ApoE−/− animals (12). These data indicate that hyperlipidemia does not worsen but rather somewhat improves renal I /R injury.…”
Section: Introductionmentioning
confidence: 72%
“…Statins administration might reduce oxidative stress, improve endothelial function and decrease inflammation [140,141]. Moreover, in experimental models of ischemiareperfusion, short-term statin treatment decreases renal dysfunction and inflammation [142,143]. Based on these data, the authors administrated high dose atorvastatin a day before surgery and continued until hospital discharge in statin naive patients; in those using statins prior to the study, treatment was administered until the day after surgery (https://www.asn-online.org/education/kidneyweek/ 2015/KW15_Late-Breakers.pdf ).…”
Section: Acute Kidney Injurymentioning
confidence: 99%